Midtrimester Cervical Length in Low-Risk Nulliparous Women for the Prediction of Spontaneous Preterm Birth: Should We Consider a New Definition of Short Cervix? - Guerby, Paul; Girard, Mario; Marcoux, Geneviève; Beaudoin, Annie; Pasquier, Jean-Charles; Bujold, Emmanuel (American Journal of Perinatology, 2021)
Objective The study aimed to estimate the predictive value of midtrimester cervical length (CL) and the optimal cut-off of CL that should be applied with asymptomatic nulliparous women for the prediction of spontaneous preterm birth (sPTB).Study Design This is a prospective cohort study of asymptomatic nulliparous women with a singleton gestation. Participants underwent CL measurement by transvaginal ultrasound between 20 and 24 weeks of gestation. The participants and their health care providers remained blinded to the results of CL measurement. The primary outcomes were sPTB before 35 weeks and sPTB before 37 weeks. Receiver operating characteristics (ROC) curve analyses were performed. Analyses were repeated by using multiples of median (MoM) of CL adjusted for gestational age.Results Of 796 participants, the mean midtrimester CL was 40 ± 6 mm with a 1st, 5th, and 10th percentile of 25, 29, and 32 mm, respectively. ROC curve analyses suggest that a cut-off of 30 mm was the optimal CL to predict sPTB before 35 weeks (area under the ROC curve [AUC]: 0.70, 95% confidence interval [CI]: 0.56–0.85) and before 37 weeks (AUC: 0.70, 95% CI: 0.59–0.80). Midtrimester CL <30 mm could detect 35% of all sPTB before 35 weeks at a false-positive rate of 5% (relative risk: 9.1, 95% CI: 3.5–23.5, p < 0.001). We observed similar results using a cut-off of CL <0.75 MoM adjusted for gestational age.Conclusion A midtrimester CL cut-off of 30 mm (instead of 25 mm), or CL less than 0.75 MoM, should be used to identify nulliparous women at high risk of sPTB.Key Points
Keywords: cervical length; short cervix; screening; preterm birth; nulliparous